THE CRIMINAL ACTION OF EXHIBITIONISM ACCORDING TO ISLAMIC CRIMINAL LAW - Erindia, Erindia; Dewi, Rusmala; Andriyani, Andriyani (Nurani, 2021)
The result of this research is that exhibitionism actors can be caused by two factors, namely the first (internalinternal) factor, which is anfactor that comes from the actor's self which is seen from the psychological and biological side, the two (externalexternal) factors, namely thefactor. actors who can be influenced by the environment, there are no special factors that cause an exhibitionist because the causative factors depend on the condition of the actor and his environment. In Islamic Criminal Law exhibitionism is snared withpunishment, Ta'zir namely in accordance with the ijtihad judge's, the judge determines whether the perpetrator is guilty or not according to the conditions mentioned, in the Nash al-Qur'an and Hadith the punishment for exhibitionism has not been clearly regulated, because exhibitionist this is an issue that recently appeared or happened today and not yet known in ancient times because that sanctions exhibitionist according to the laws of this research includesresearch, empiricalwhereas the specification of this research is qualitative descriptiveanalysis,pedekatan main pursued is obtained through approaches with the law and approach to cases that occur in some areas. Keywords: Exhibitionist, Law Number 44 Year 2008 Pornography, Ta'zir